Pengaruh Gamifikasi Berbasis Media Monopoli terhadap Pemahaman Gramatika Bahasa Arab - Nazilah, Luluk; Syarifuddin, Syarifuddin; Syaifullah, Syaifullah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Educational media is one of the methods to enhance the teaching and learning process, making students more active in their learning. As a result, the learning outcomes align with expectations. The aim of this study is to investigate the effect of Monopoly-based gamification on students' understanding of Arabic grammar. This study is an experimental research with a one-group pre-test post-test design using a quantitative research method. The research sample consisted of 26 ninth-grade students. The research instruments were pre-test and post-test assessments to measure students' understanding before and after the implementation of the Monopoly media. The results showed a significant improvement in students' grammatical understanding after the implementation of the Monopoly media, with the average pre-test score of 55.96 increasing to 68.27 in the post-test. Normality tests for the pre-test and post-test results showed significant values of 0.149 and 0.116, respectively, both exceeding the threshold of 0.05. This indicates that the data are normally distributed. Furthermore, the paired t-test results showed a two-tailed significance value of 0.001, indicating that Monopoly-based gamification can significantly improve students' understanding of Arabic grammar. The application of Monopoly media also encourages social interaction and collaboration among students in the learning process.